Pelaksanaan Project Citizen Mahasiswa Prodi Teknik Penerbangan Universitas Dirgantara Marsekal Suryadarma Melalui Pembelajaran Berbasis Proyek Pada Mata Kuliah Pendidikan Kewarganegaraan - Ardison Asri Asri; Ario Wendra; Aria Caesar Kusuma Atmaja (FTK UNSURYA, 2026)
This study aims to describe project-based learning in the Citizenship Education module and its implementation for students of the Aviation Engineering Programme at Unsurya, as an effort to instil civic skills. The research employed a descriptive qualitative method, with data gathered through classroom observation and literature study concerning project-based learning in the Citizenship Education module. The findings indicate that the implementation of project-based learning in the Citizenship Education module by the Aviation Engineering students has been quite successful. This is evidenced by the outcomes of the group projects: Group One produced a campaign titled “Anti-Corruption Education”, and Group Two created a campaign entitled “Stop Violence on Campus”. The success of these projects represents a meaningful step in instilling civic skills, aiming to enhance communication abilities, develop teamwork across diverse backgrounds, raise awareness of the importance of a strong safety culture and high integrity in the aviation industry, sharpen analytical thinking, and prepare students to become competent professionals who contribute positively to society and the aviation sector.